2018
DOI: 10.1590/0074-02760170421
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species generation mediated by NADPH oxidase and PI3K/Akt pathways contribute to invasion of Streptococcus agalactiae in human endothelial cells

Abstract: BACKGROUND Streptococcus agalactiae can causes sepsis, pneumonia, and meningitis in neonates, the elderly, and immunocompromised patients. Although the virulence properties of S. agalactiae have been partially elucidated, the molecular mechanisms related to reactive oxygen species (ROS) generation in infected human endothelial cells need further investigation.OBJECTIVES This study aimed to evaluate the influence of oxidative stress in human umbilical vein endothelial cells (HUVECs) during S. agalactiae infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…(13) GBS90356 isolate was cultured on blood agar base (BAB; Oxoid, Cambridge, UK) plates containing 5% sheep defibrinated blood for 24 h at 37ºC and then grown in Brain Heart Infusion broth (BHI; Difco Laboratories Inc, Detroit, MI, USA) at 37ºC until an optical density (OD) of 0.4 at ƛ = 540 nm (~10 8 CFU/mL) was reached. (11) HUVEC culture -Primary HUVEC were obtained by treating umbilical veins with 0.1% collagenase IV solution (Sigma Chemical Co., St. Louis, MO, USA) as previously described. (11) Cells were used during first or second passages only, and subcultures were obtained by treating the confluent cultures with 0.025 % trypsin/0.2 % EDTA solution in phosphate-buffered saline (PBS) (150 mM NaCl, 20 mM phosphate buffer, pH 7.2 -all from Sigma Chemical Co., St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…(13) GBS90356 isolate was cultured on blood agar base (BAB; Oxoid, Cambridge, UK) plates containing 5% sheep defibrinated blood for 24 h at 37ºC and then grown in Brain Heart Infusion broth (BHI; Difco Laboratories Inc, Detroit, MI, USA) at 37ºC until an optical density (OD) of 0.4 at ƛ = 540 nm (~10 8 CFU/mL) was reached. (11) HUVEC culture -Primary HUVEC were obtained by treating umbilical veins with 0.1% collagenase IV solution (Sigma Chemical Co., St. Louis, MO, USA) as previously described. (11) Cells were used during first or second passages only, and subcultures were obtained by treating the confluent cultures with 0.025 % trypsin/0.2 % EDTA solution in phosphate-buffered saline (PBS) (150 mM NaCl, 20 mM phosphate buffer, pH 7.2 -all from Sigma Chemical Co., St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…(11) HUVEC culture -Primary HUVEC were obtained by treating umbilical veins with 0.1% collagenase IV solution (Sigma Chemical Co., St. Louis, MO, USA) as previously described. (11) Cells were used during first or second passages only, and subcultures were obtained by treating the confluent cultures with 0.025 % trypsin/0.2 % EDTA solution in phosphate-buffered saline (PBS) (150 mM NaCl, 20 mM phosphate buffer, pH 7.2 -all from Sigma Chemical Co., St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phosphorylation of Beclin1 mediated by protein kinase B (AKT) functions in oncogenesis and autophagy inhibition [19]. Meanwhile, the phosphoinositide 3-kinase (PI3K)/AKT signaling pathway mediated by a pathogen contributes to coordination of actin rearrangement, thereby leading to internalization of the organism [20]. A study has suggested that the activated PI3K/AKT/mammalian target of rapamycin (mTOR) signaling pathway is implicated in lung tumorigenesis and it has been related to high-grade tumors and advanced diseases [21].…”
Section: Introductionmentioning
confidence: 99%